Safety, pharmacokinetics, and mosquito‐lethal effects of ivermectin in combination with dihydroartemisinin‐piperaquine and primaquine in healthy adult Thai subjects - Kobylinski, KC; Jittamala, P; Hanboonkunupakarn, B; Pukrittayakamee, S; Pantuwatana, K; Phasomkusolsil, S; Davidson, SA; Winterberg, M; Hoglund, RM; Mukaka, M; Van Der Pluijm, RW; Dondorp, A; et al. (American Society for Clinical Pharmacology and Therapeutics, 2019)
Mass administration of antimalarial drugs and ivermectin are being considered as potential accelerators of malaria elimination. The safety, tolerability, pharmacokinetics and mosquito-lethal effects of combinations of ivermectin, dihydroartemisinin-piperaquine, and primaquine were evaluated. Co-administration of ivermectin and dihydroartemisinin-piperaquine, resulted in increased ivermectin concentrations with corresponding increases in mosquito-lethal effect across all subjects. Exposure to piperaquine was also increased when co-administered with ivermectin, but electrocardiograph QT-interval prolongation was not increased. One subject had transiently impaired liver function. Ivermectin mosquito-lethal effect was greater than predicted previously against the major Southeast Asian malaria vectors. Both Anopheles dirus and Anopheles minimus mosquito mortality was increased substantially (20-fold and 35-fold increase, respectively) when feeding on volunteer blood after ivermectin administration compared to in vitro ivermectin-spiked blood. This suggests the presence of ivermectin metabolites that impart mosquito-lethal effects. Further studies of this combined approach to accelerate malaria elimination are warranted.